IoT E-business applications - Bucea-Manea-Tonis, Radu; B. Manea Tonis, Rocsana (Journal of Economic Development, Environment and People, 2017)
“Internet of things” (IoT) will develop soon an ecosystem of internet-connected things, that facilitate the mobile commerce experiences and the client need to be informed all the time. It will be associated with a feeling of freedom and capacity of doing very easy what was considered difficult in the past. Nevertheless, these opportunities will not be capitalized upon without overcoming a series of obstacles, including addressing consumer privacy concerns, the long replacement cycles of durable goods and the standardization of operating platforms. Modern E-business web applications are now developed using new technologies such as NodeJS, AngularJS and Bootstrap. The article identifies and solves practical issues regarding the JSON exchanged messages between NodeJS and AngularJS within SMEs E-business environment.